Quantum chemistry : Including molecular spectroscopy - Sen, B.K. (New Delhi, India : Tata McGraw-Hill Publishing Company Limited, 1992)
This book is designed mainly for T.D.C. (Major) students as well as for first year postgraduate students of different Indian Universityes. It discusses the fundamentals of quantum mechanics and their application to chemical bonding and molecular spectroscopy.